Recovery of dehydrogenase enzymes activities Heteropneustes fossilis (Bloch) exposed to sublethal levels of mercury - James, R; Sampath, K; Devakiamma, G; Pattu, V Jancy (Indian Journal of Fisheries, 2011)
The impact of sublethal levels of mercury on the activities of succinate dehydrogenase (SDH) and Glyceroldehyde dehydrogenase (GDH) enzymes in different tiBsues of Heterapneustes tassilis were studied. Recovery of enzyme activities were also assessed. Sublethal concentrations of mercury inhibited the SDH activity and enhanced the GDH activity in all tested tissues; the inhibition and enhancement were concentration dependent. This suggests the suppression of oxidative metabolism and triggering of anaerobic metabolism to derive energy during metal stress. Metal exposed animals when shifted to metal impoverished water, showed recovery in the activity of both enzymes, however, it was not complete.